Visual Distraction During Sleep Induction with Propofol in Pediatric Patients – Can Cartoon Watching Influence the Sedative Dose? - Tschiedel, Eva; Beckers, Kristina; Große-Lordemann, Anja; Basu, Oliver; Felderhoff-Müser, Ursula; Dohna-Schwake, Christian (Klinische Pädiatrie, 2019)
Background In general anesthesia, cartoon watching and playing video games reduce anxiety in children. It is unknown whether watching a video in the intervention room has a similar effect, and therefore is able to reduce sedative doses in children undergoing small medical procedures. Aim of this prospective study was to determine the effect of watching a standardized cartoon immediately before and during sleep induction for deep sedation on consumption of propofol in children.Patients and Methods 50 children aged 2–14 years undergoing deep sedation were randomly assigned to 2 groups: (A) watching or (B) not watching a standardized videoclip during sleep induction with propofol. The achievement of predefined sedation depth was objectified by measuring Comfort Score (aim 10–14) and Bispectral Index (aim 50–60).Results The median sleep induction dose of propofol did not differ in both groups (A: 1.76 (0.62–4.37) mg/kg; B: 1.37 (0.66–5.26) mg/kgKG; p=0.65). Cartoon watching was associated with shorter sleep onset latency (A: 120 (60–480)s; B: 240 (40–600)s; p=0.043). Subgroup analysis reveals this especially for school children and girls. In both groups no complications occurred.Conclusion Children watching a standard cartoon during sleep induction for deep sedation have a shorter sleep onset time but sedative dose is not reduced.
Keywords: sedation; sedative dose; children; cartoon; distraction